Ecological diversification in sexual and asexual lineages - P. Catalina Chaparro-Pedraza; Gregory Roth; Carlos J. Melián (Scientific Reports, 2024)
Abstract The presence or absence of sex can have a strong influence on the processes whereby species arise. Yet, the mechanistic underpinnings of this influence are poorly understood. To gain insights into the mechanisms whereby the reproductive mode may influence ecological diversification, we investigate how natural selection, genetic mixing, and the reproductive mode interact and how this interaction affects the evolutionary dynamics of diversifying lineages. To do so, we analyze models of ecological diversification for sexual and asexual lineages, in which diversification is driven by intraspecific resource competition. We find that the reproductive mode strongly influences the diversification rate and, thus, the ensuing diversity of a lineage. Our results reveal that ecologically-based selection is stronger in asexual lineages because asexual organisms have a higher reproductive potential than sexual ones. This promotes faster diversification in asexual lineages. However, a small amount of genetic mixing accelerates the trait expansion process in sexual lineages, overturning the effect of ecologically-based selection alone and enabling a faster niche occupancy than asexual lineages. As a consequence, sexual lineages can occupy more ecological niches, eventually resulting in higher diversity. This suggests that sexual reproduction may be widespread among species because it increases the rate of diversification.